2016
DOI: 10.1016/j.clindermatol.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of the light: Phototherapy adverse effects

Abstract: Phototherapy is a valuable therapeutic tool in Dermatology, but there may be drawbacks. Acute and long-term adverse effects, of variable severity, include skin erythema, xerosis, pruritus, blistering, altered pigmentation, photoaging, and photocarcinogenesis. Despite concerns over the carcinogenic potential of ultraviolet radiation, most studies have not found an increased risk of non-melanoma or melanoma skin cancer in patients treated with ultraviolet B (broadband and narrowband) and ultraviolet A1 photother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 58 publications
0
22
0
2
Order By: Relevance
“…However, there have been problems noted with light treatments; for example, Valejo Coelho and Apetato [1] did a study on adverse effects of phototherapy which could lead to certain skin cancers. In addition, other studies from Wickremasinghe et al [2] and Frazier et al [3] have noted a significant increased risk of cancer in infants after neonatal phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been problems noted with light treatments; for example, Valejo Coelho and Apetato [1] did a study on adverse effects of phototherapy which could lead to certain skin cancers. In addition, other studies from Wickremasinghe et al [2] and Frazier et al [3] have noted a significant increased risk of cancer in infants after neonatal phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A few explanations were possible for our results. First, the 308nm EL treatment does not have carcinogenic potential as the previous studies for NBUVB showed no significant increment in skin cancers (Archier et al, 2012;Hearn et al, 2008;Valejo Coelho & Apetato, 2016). Second, EL treatment, which consists of irradiation of the depigmented lesions sparing perilesional skin, could prevent cutaneous immunosuppression and mutagenesis by UV irradiation in uninvolved skin.…”
Section: Discussionmentioning
confidence: 94%
“…There have been long‐standing concerns regarding the risks of skin cancer following phototherapy in patients with psoriasis and vitiligo. Previous studies reported an increased risk of skin cancer following photochemotherapy such as psoralens with ultraviolet A (PUVA) phototherapy (Stern & Laird, ; Stern et al, ; Valejo Coelho & Apetato, ). In contrast, the potential role of narrowband UVB (NBUVB) in photocarcinogenesis is still controversial, but recent studies suggested no significant association between NBUVB treatment and skin cancers (Archier et al, ; Hearn, Kerr, Rahim, Ferguson, & Dawe, ; Valejo Coelho & Apetato, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It puts forefront the possibility of using oral calcidiol in the management of AD patients, as it yielded results that appeared to be comparable to that of NB-UVB that is regarded as the most efficacious, well-tolerated treatment option for AD [2,23]. This could be of particular value as it overcomes the compliance problem that is commonly faced while using phototherapy [24], and has a higher safety profile when the side effects of phototherapy [25], or even topical steroids [26] are considered. The use of oral calcidiol in the management of AD has been proven before to be successful [9,22,[27][28][29][30].…”
Section: Groupmentioning
confidence: 99%